A produção do discurso socioespacial nos escritos de Ivan Fernandes Lima: popularização do conhecimento geográfico a partir do uso dos jornais - Almeida, Ricardo Santos de (2025)
This thesis is based on different geographic statements written in newspapers by Ivan Fernandes Lima and highlights his contribution to Geography. It is considered that the multiple socio-spatial dynamics are latent in the writings and are evidenced in the problematizations about the state of Alagoas. His knowledge involves the (re)production of space, the transformations of landscapes, hunger, the search for developmentalism, and its use can be encouraged for the different levels of teaching-research-extension, corroborating the understanding of socio-spatial dynamics of times-spaces of yesteryear in the light of contemporaneity. Thus, one hundred and twenty-three texts published from 1961 to 1978 by the geographer were analyzed, as well as interviews and reports conducted with him. In this sense, geographic discourses are understood as statements (Foucault, 2017) that are characterized as a determined way of ordering available knowledge that is activated through rules for established relations that are current and possible from the praxis and discursive formations in evidence. The object (sociospatial discourses) comes to be understood through a similar set that differs from each other, but that does not change, since the being of language, the signs corroborate to establish the bundle of relations emerging the nexus that permeates the apprehension and acquisition of knowledge from the triad signifier-signified-referent. The intention of this thesis is not to verify whether what was said or written was put into practice with regard to sociospatial dynamics, since discourse is confirmed by action, since, in the territory of language, it is necessary to conceive how the things that are spoken, written and pronounced mean. Therefore, it is necessary, in Geography, to deconstruct the idea that journalistic writings are mere time-spatial excerpts, and place them in the place/status of producers of geographical knowledge.